Effects of oral liquiritigenin inoculation on gut microbiota and gene expression in intestinal and extraintestinal tissues of mice - Suo, Zhaotaize; Yu, Ying; Shi, Fangyun; Tian, Jijing; Hao, Zhihui; Zhang, Jingren; Zou, Jun (Frontiers in Microbiomes, 2024)
IntroductionLiquiritigenin (LQ), a natural flavonoid found in traditional Chinese medicine and often administered orally, holds potential to affect both the gut and its microbiota, that potentially mediating or influencing its biological and pharmacological effects. However, the effects of LQ on gut microbiota composition and intestinal function remain poorly understood. In this study, we aimed to explore the impact of LQ on gut microbiota and gene expression in both intestinal and extraintestinal tissues.MethodsWe orally inoculated six-week-old SPF C57BL/6 mice with either LQ (a concentration of 4 mg/ml diluted in dimethylsulfoxide, (DMSO)) or DMSO, and administered daily for a duration of 2 weeks. At the end of the experimental period, all mice were euthanized. Fresh fecal samples, as well as samples from the intestine, lung, and liver, were collected for subsequent microbiota analysis, RNA-seq, or histochemical and immunohistochemical (IHC) staining.ResultsFindings show that LQ alters gut microbiota composition, enhancing microbial correlations in the colon but causing some dysbiosis, evidenced by increased pathobionts, decreased beneficial bifidobacteria, and reduced microbiota diversity. Gene expression analysis reveals LQ upregulates mucosal immune response genes and antiinfection genes in both the intestine and lung, with histology confirming increased Paneth cells and antimicrobial peptides in the intestine. Additionally, LQ affects tissue-specific gene expression, triggering hypersensitivity genes in the colon, downregulating metabolic genes in the small intestine, and reducing cell motility and adhesion genes in the lung.DiscussionThese results suggest LQ’s potential to modulate common mucosal immunity but also highlight possible risks of gut dysbiosis and hypersensitivity, particularly in vulnerable individuals. Our study, while informative about the effects of LQ on gut health, lacks direct evidence on whether changes in gut microbiota and gene expression caused by LQ impact inflammatory diseases or are causally linked. Future research should investigate this through fecal microbiota transplantation to explore the causal relationships and LQ’s potential effects on immune responses and disease outcomes in relevant models.